1017. ASARUM SIEBOLDII FORMA MACULATUM: Aristolochiaceae. (11th June 2022) - Moore, Richard; King, Christabel
Summary: Asarum sieboldii f. maculatum (Nakai) Yamaji is a low growing, deciduous rhizomatous herb endemic to South Korea. It is illustrated here with a painting, a line drawing and a photograph in the wild; its introduction, horticultural merits and cultivation are discussed. Recent research has shown that the plain‐leaved A. sieboldii Miq. and A. maculatum Nakai are conspecific, and the rank of forma has been chosen here to denote the plant with mottled leaves.